The Influence of Fast Food Diet on The Incidence of Obesity in School Children : A Systematic Review - Pangkahila, Evangelista Maria; Pangkahila, Jahja Alex (International Medical Journal Corp. Ltd, 2024)
Backgrounds : Obesity occurs due to an imbalance between incoming and outgoing energy intake, so excess energy is stored as fat tissue. The prevalence of overweight and obese children in the world in 2010 was 6.7%, increasing to 9.1% in 2020. Frequent consumption of ready-to-eat foods can increase the incidence of obesity. Fast food usually contains large amounts of sodium, saturated fat, and cholesterol. Aims : This systematic review aims to determine the effect of fast food on the incidence of obesity in school children. Method : This study used a systematic review approach. The research data source used scientific journals that met the inclusion and exclusion criteria. Result : Based on nine scientific articles analyzed, seven journals showed that the habitual pattern of fast food consumption can increase the incidence of obesity in children, and two journals showed no effect of fast food consumption on obesity. Conclusion : Fast food consumption patterns in school children occur due to technological developments and cultural changes. Therefore, it is necessary to change behaviour and eating patterns in school children.